Analisis Struktur, Fungsi dan Makna Mantra Penunduk dan Pelindung Badan Suku Anak Dalam Jambi Kelompok Air Hitam Taman Nasional Bukit Duabelas Sarolangun Jambi - Andiopenta Andiopenta (Universitas Batanghari Jambi, 2022)
The Suku Anak Dalam Jambi are one of the tribes that are still isolated in Jambi Province. In social life, they still believe in the existence of spells. Mantra is a series of words that have certain conditions which are believed to contain supernatural powers and are passed down from generation to generation in various ethnic groups in Indonesia. Likewise for the Anak Dalam Tribe who inhabit the Bukit 12 Sarolangon settlement, Jambi Province. Mantras that are believed by the Suku Anak Dalam (Kubu) community can be a guide in various aspects of their lives. However, in this article, the spells analyzed are limited to subduing and body armor. Mantra is a series of words that have certain conditions which are believed to contain magical powers that are passed down from generation to generation. The mantra that is believed by the Suku Anak Dalam Jambi community is believed to be able to subdue someone and be able to protect themselves. The structure, function, and meaning of mantras in the Suku Anak Dalam Jambi community, both subservient and protective spells, have a free structure, or include free poetry, free rhyme, not bound by stanzas and lines. In addition, it does not make a rhyming sound. The sound of language that arises is only simple, in this case it lacks hearing power that is able to arouse feelings through the five senses of hearing, like a poem. The meanings that arise from the choice of words used are grammatical meanings and use connotative diction.